Intermodal, Urban, Mobile – Characterization of Intermodal Trips and Users Taking the Example of Berlin - Jarass, Julia; Oostendorp, Rebekka (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
Intermodal travel behaviour – the combination of different modes on a single trip – is increasingly taken into consideration in everyday mobility. In particular, urban areas face negative consequences from high car traffic and scarce parking space. Simultaneously, larger cities often have a well-developed public transport system and good accessibility by bike or on foot, which allows the use of other modes than the car. Intermodal travel behaviour enables an individual and flexible mobility. This means that persons rather use and combine different transport modes according to their specific travel needs than committing themselves to one single mode of transport. On the contrary, the use of more than one mode of transport also requires more extensive planning of the trips, the willingness to change, and specific mobility skills and information. Using the example of Berlin, this article discusses intermodal travel behaviour in the context of everyday mobility in European cities. Therefore, we analyse the amount and the specific characteristics of intermodal trips. Then, persons with intermodal travel behaviour are identified and examined in comparison to unimodal reference groups. The results show that only a small amount of trips is currently intermodal. These trips are on average longer than unimodal trips and are routine trips (e.g., trips to work) covered by two or more different modes of transport. Moreover, intermodal users differ from unimodal users: persons who combine two or more transport modes on work trips tend to be younger, female, and have a higher education level. They have diverse mobility resources available in their households, although they have to plan their usage with other household members. Furthermore, intermodal travel behaviour varies depending on the residential location within the city. The findings suggest that specific user groups and their demands must be addressed when expanding and optimizing intermodal mobility options.